How topography induces reproductive asynchrony and alters gypsy moth invasion dynamics. (4th August 2014) - Walter, Jonathan A.; Meixler, Marcia S.; Mueller, Thomas; Fagan, William F.; Tobin, Patrick C.; Haynes, Kyle J.; Hambäck, Peter
Summary Reproductive asynchrony, a temporal mismatch in reproductive maturation between an individual and potential mates, may contribute to mate‐finding failure and Allee effects that influence the establishment and spread of invasive species. Variation in elevation is likely to promote variability in maturation times for species with temperature‐dependent development, but it is not known how strongly this influences reproductive asynchrony or the population growth of invasive species. We examined whether spatial variation in reproductive asynchrony, due to differences in elevation and local heterogeneity in elevation (hilliness), can explain spatial heterogeneity in the population growth rate of the gypsy moth, Lymantria dispar (L.), along its invasion front in Virginia and West Virginia, USA. We used a spatially explicit model of the effects of reproductive asynchrony on mating success to develop predictions of the influences of elevation and elevational heterogeneity on local population growth rates. Population growth rates declined with increased elevation and more modestly with increased elevational heterogeneity. As in earlier work, we found a positive relationship between the population growth rate and the number of introduced egg masses, indicating a demographic Allee effect. At high elevations and high heterogeneity in elevation, the population growth rate was lowest and the density at which the population tended to replace itself (i.e. the Allee threshold) was highest. An analysis of 22 years of field data also showed decreases in population growth rates with elevation and heterogeneity in elevation that were largely consistent with the model predictions. These results highlight how topographic characteristics can affect reproductive asynchrony and influence mate‐finding Allee effects in an invading non‐native insect population. Given the dependence of developmental rates on temperature in poikilotherms, topographic effects on reproductive success could potentially be important to the population dynamics of many organisms.